Assessing typhoon impacts on mangroves and post-typhoon recovery patterns to inform projects using mangroves as nature-based solutions - Xueqin Gao; Felix Leung; Wenqing Wang (Global Ecology and Conservation, 2025)
On July 18, 2014, Super Typhoon Rammasun caused significant damage to a mangrove forest at Dongzhaigang Bay, Hainan Island. To evaluate the structural damage and recovery patterns of mangrove forests, vegetation in permanent plots was surveyed at 1, 12, and 24 months after the event. Six mangrove species were assessed, including five native species (Kandelia obovata, Bruguiera sexangula, Rhizophora stylosa, Avicennia marina, and Ceriops tagal) and one exotic species (Sonneratia apetala). Results revealed that mangroves exhibited species-specific resistance and resilience to the super typhoon. S. apetala and B. sexangula were the most severely affected, followed by K. obovata, R. stylosa, and A. marina. C. tagal was the least impacted, indicating its high resistance. The extent of damage at community level had a significant positive correlation with basal diameter and tree height, and a negative correlation with the tree density. S. apetala, A. marina, and R. stylosa displayed rapid recovery after the event, indicating their high resilience. However, B. sexangula and K. obovata had notably high mortality one year after the disturbance. Species traits (e.g. refoliation or resprouting) interact with environmental factors such as changes in hydrology in producing post-hurricane recovery patterns. Damage and recovery from storms varies among species indicating that diverse assemblages are important for sustainability of projects using mangroves as nature-based solutions under a changing climate with increasing storm strength and frequency.